A new mild, clean and highly efficient method for the preparation of graphene quantum dots without by-products1. Issue 34 (14th September 2015) - Zhu, Chong; Yang, Siwei; Wang, Gang; Mo, Runwei; He, Peng; Sun, Jing; Di, Zengfeng; Kang, Zhenhui; Yuan, Ningyi; Ding, Jianning; Ding, Guqiao; Xie, Xiaoming
<x xml:space="preserve">Abstract</x> We demonstrated that graphene oxide can be oxidized and cut into graphene quantum dots by hydroxyl radicals which is obtained by catalytic decomposition of hydrogen peroxide with a tungsten oxide nanowire catalyst.